The name of the trout: considerations on the taxonomic status of the Salmo trutta L., 1758 complex (Osteichthyes: Salmonidae) in Italy. Issue 1 (1st January 2019) - Splendiani, A.; Palmas, F.; Sabatini, A.; Caputo Barucchi, V.
Abstract: The systematic status of the Italian trout in the Salmo trutta L., 1758 complex (including marble, Mediterranean and lacustrine trout), has long been - and is still today – subject of controversies among ichthyologists. The specific name and the taxonomic rank changed several times in the last years, and the natural occurrence of this salmonid fish in some Italian areas was debated due to spread of alien strains. The main difficulty with the taxonomy of the Italian trout stems from the impossibility of disentangling it "on paper" or, even worse, trying to face this systematic issue considering only a very limited (local/national scale) part of the brown trout range. The taxonomy of the Italian trout population is inextricably linked to the necessity of clarifying first phylogeny and phylogeography in an overall Mediterranean context. The opportunity of a non "self-referential" taxonomy is even more fundamental for a vulnerable salmonid like the Italian brown trout, for which there is a very conflicting management problem related to sport fishing and, at the same time, the urgent need for effective conservation measures. It is however necessary to emphasize that conservation is independent from taxonomy but must start from the level of the local population. In fact, management units need stability and they cannot, therefore, coincide with entities – the Linnean species – requiring continuous taxonomic revisions. Modern molecular methods are the best tools for defining these units of management and conservation in an evolutionary perspective.